Magnetic Resonance Imaging in sonographically indeterminate adnexal masses - Joori, Salam M.; Fadhil, Atheer A.; Abdullateef, Wassen M.; Jabir, Maysoon M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Although ultrasonography (US) continues to be the primary imaging modality used to identify and characterize adnexal masses, but certain conditions that hinder accurate ultrasound examination, such as obesity, may be indications for magnetic resonance (MR) imaging, for the assessment of complex and indeterminate ovarian masses. Objective: to assess the ability of MRI to characterize sonographically indeterminate adnexal masses. Patients and methods: A prospective study of 89 cases with sonographically indeterminate adnexal mass underwent pelvic MRI conducted in X-ray institute in medical city in Baghdad during period from October 2011 to January 2013 & the results compared to the final diagnosis which was determined by histopathological & surgical findings Results: Most sonographyically indeterminate adnexal masses result from common benign condition. Benign conditions account for 87.6%, while malignant condition account for 12.4%. Endometriosis was the commonest cause constitute (22.4 %), followed by mature cystic teratoma , and pedunculated fibroid (18%) and (15.7%) respectively. Excellent agreement was noted between MRI and final diagnosis for determining the origin and tissue characteristics which are 98% and 91% respectively. Conclusion: Sonographically indeterminate adnexal masses of uncertain origin and solid or complex content will benefit from further evaluation with MRI, which is highly accurate for identifying the origin of the mass and characterizing its tissue contents playing an important role in planning the way of management.